Lipid analysis : isolation, separation, identification and lipidomic analysis - Christie, William W. (Oily Press lipid library, 2010)
Brought up to date because of the pace of developments in mass spectrometry of intact lipids, which has given recognition of lipid analysis and 'lipidomics' as a distinct science. Although devoting considerable space to mass spectrometry and lipidomics, remains a practical guide to the complexities of the analysis of lipids. As in past editions, it is designed to act as a primary source, of value at the laboratory bench rather than residing on a library shelf.